What Is the Impact of Surgical Approach in the Treatment of Degenerative Cervical Myelopathy in Patients With OPLL? A Propensity-Score Matched, Multi-Center Analysis on Inpatient and Post-Discharge 90-Day Outcomes. Issue 2 (March 2023) - Lee, Nathan J.; Boddapati, Venkat; Mathew, Justin; Fields, Michael; Vulapalli, Meghana; Kim, Jun S.; Lombardi, Joseph M.; Sardar, Zeeshan M.; Lehman, Ronald A.; Riew, K. Daniel
Study Design: Retrospective cohort. Objective: Provide a comparison of surgical approach in the treatment of degenerative cervical myelopathy in patients with OPLL. Methods: A national database was queried to identify adult (≥18 years) patients with OPLL, who underwent at least a 2-level cervical decompression and fusion for cervical myelopathy from 2012-2014. A propensity-score-matching algorithm was employed to compare outcomes by surgical approach. Results: After propensity-score matching, 627 patients remained. An anterior approach was found to be an independent predictor for higher inpatient surgical complications(OR 5.9), which included dysphagia:14%[anterior]vs.1.1%[posterior] P -value < 0.001, wound hematoma:1.7%[anterior]vs.0%[posterior] P -value = 0.02, and dural tear:9.4%[anterior]vs.3.2%[posterior] P -value = 0.001. A posterior approach was an predictor for longer hospital length of stay by nearly 3 days(OR 3.4; 6.8 days[posterior]vs.4.0 days[anterior] P -value < 0.001). The reasons for readmission/reoperation did not vary by approach for 2-3-level fusions; however, for >3-level fusions, patients with an anterior approach more often had respiratory complications requiring mechanical ventilation( P -value = 0.038) and required revision fusion surgery( P -value = 0.015). Conclusions: The national estimates for inpatient complications(25%), readmissions(9.9%), and reoperations(3.5%) are substantial after the surgical treatment of multi-level OPLL. An anterior approach resulted in significantly higher inpatient surgical complications, but this did not result in a longer hospital length of stay and the overall 90-day complication rates requiring readmission or reoperation was similar to those seen after a posterior approach. For patients requiring >3-level fusion, an anterior approach is associated with significantly higher risk for respiratory complications requiring mechanical ventilation and revision fusion surgery. Precise neurological complications and functional outcomes were not included in this database, and should be further assessed in future studies.